The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1186/s12889-016-3672-y
|View full text |Cite|
|
Sign up to set email alerts
|

Gender difference and effect of pharmacotherapy: findings from a smoking cessation service

Abstract: BackgroundSmoking cessation services are available in England to provide assistance to those wishing to quit smoking. Data from one such service were analysed in order to investigate differences in quit rate between males and females prescribed with different treatments.MethodsA logistic regression model was fitted to the data using the binary response of self-reported quit (failed attempt = 0, successful attempt = 1), validated by Carbon Monoxide (CO) monitoring, 4 weeks after commencing programme. Main effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 44 publications
4
10
0
1
Order By: Relevance
“…Age-based results imply greater difficulty amongst the young (teenagers and the 20–29 year old group in this instance) in quitting, as has been reported elsewhere [ 28 ]. This age group is an important one to reach and support, given that the long term benefits of cessation are greater at this stage of life than amongst those of an older age [ 1 ].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Age-based results imply greater difficulty amongst the young (teenagers and the 20–29 year old group in this instance) in quitting, as has been reported elsewhere [ 28 ]. This age group is an important one to reach and support, given that the long term benefits of cessation are greater at this stage of life than amongst those of an older age [ 1 ].…”
Section: Discussionsupporting
confidence: 80%
“…These data show that average cost per quit amongst males was slightly reduced relative to females, a finding which is consistent with men being more likely to quit in the context of smoking cessation services [ 28 , 30 ], although the magnitude of the difference was not great when considered against the overall average costs observed (difference = £18.70 at 12 weeks). If the reason behind the different quit rates between men and women was related to anxiety about weight gain due to quitting smoking, the provision of a more comprehensive service combining both smoking cessation and weight loss may be worth considering [ 31 ].…”
Section: Discussionsupporting
confidence: 71%
“…(Brose et al, 2013; Prado et al, 2011; Ucar et al, 2014)); however gender differences in real-world effectiveness are understudied. Walker et al (2016) studied such differences using data from a national quit service in the United Kingdom, Quit-5. Their findings demonstrated that women were less likely than men to achieve 12-week abstinence, and that the relative advantage of varenicline over NRT was significantly greater for women compared to men.…”
Section: Introductionmentioning
confidence: 99%
“…We used data recorded on clients registered with Quit 51 , a provider of smoking cessation services in England, to test whether the increased quit rates expected with varenicline versus NRT are moderated by other factors (such as age, gender, ethnic group and features of service provision). An earlier analysis of data from Quit 51 focused on interactions with gender including treatment . The current work takes in approximately 6 months of further data (up to September 2015 in previous analysis, now up to March 2016) in addition to records from seven extra regions, for which data were not available in this earlier analysis.…”
Section: Introductionmentioning
confidence: 99%